Lossy coding and bitrate effects on changes in formant frequencies in Japanese and English speech signals - Kucharski, Mateusz Andrzej; Brachmański, Stefan (International Journal of Electronics and Telecommunications, 2024)
Since speaker recognition and verification became heavily used technology, both in professional applications like forensics and more everyday ones, the question arose: what factors can impact results of those processes? One thing that may be important with respect to this subject is lossy coding, as some of the information contained in an original file is lost in the coding process. In the era of globalization, not only native languages or languages of neighboring countries are of interest to researchers, but also those quite far, especially from Asia – the biggest exporter of goods and services to Europe. Those economic relationships are usually connected with the interchange of personnel, which further shortens geographical distance. The article presents the results that are a continuation of research on the behavior of Japanese language formants. Earlier research focused on changes occurring for the first and second formants. This article presents changes observed for the third and fourth formants. The knowledge of these changes is indicated in the process of speaker identification in forensics using the spectrographic method. At the Department of Acoustics and Multimedia, Wroclaw University of Science and Technology and in many centers around the world, the auditoryspectrographic method is used, which is a combination of the aural and spectrographic methods. In the spectrographic part, a person is identified on the basis of a comparison of the formants’ trajectory.